Evaluation of an improved closed-vessel conductively heated digestion system for the analysis of raw meat samples by ICP techniques - Vieira, Alan Lima [UNESP]; Miranda, Kelber; Virgilio, Alex [UNESP]; Ferreira, Edilene Cristina [UNESP]; Gomes Neto, José Anchieta [UNESP] (Royal Society of Chemistry (RSC), 2018)
In this work, an improved conductively heated digestion system (CHDS) with closed vessels, which provides simpler, easier and safer digestion of raw chicken, beef and pork meat samples aiming at Ca, Cu, Fe, K, Mg, Mn, Na, P, S, and Zn determinations by ICP OES and As, Cd, Cr, Mo, Pb and Se by ICP-MS/MS was evaluated. For purposes of safety, easy operation, and analytical performance, a novel polytetrafluoroethylene lid with a screw valve which enables pressure relief without touching the pressurized vessel at the end of the digestion was developed for the CHDS vessels. The accuracy was checked by the analysis of three meat certified reference materials (CRMs) and the results obtained for the CHDS were compared to those of microwave-assisted digestion (MW). Blank values and carbon contents in digested samples using the CHDS were comparable to those of MW, being adequate for ICP OES and ICP-MS techniques. The recoveries for the analytes in the three CRMs varied from 85 to 110% when using the CHDS. The results found by the proposed CHDS were in agreement with those obtained by the MW comparative procedure. The limit of quantification (LOQ) values for the CHDS may be considered comparable to those of MW and adequate for raw meat analysis. The CHDS is an interesting alternative for macronutrients, micronutrients, and contaminants, and highlighted mainly the volatile elements (As, Cd, Pb and Se), which could be easily lost with open-vessel digestion systems.